Scalable physical coloration. (November 2016) - Oller, Declan; Fernandes, Gustavo E.; Siontas, Stylianos; Xu, Jimmy; Pacifici, Domenico
Graphical abstract: Highlights: ⿢ Three methods for producing coloration on Aluminum surfaces are investigated. ⿢ The methods are chosen for their scalability and their tunability. ⿢ It is shown how combinations of the methods could find widespread industrial use. Abstract: Methods to produce colored surfaces using physical mechanisms are proposed, with aluminum used as a demonstration vehicle. Our approach aims to achieve tunable, vibrant colors through the interaction of three well-established physical mechanisms of color formation, namely (1) resonant scattering and interference effects in a nano-structured surface (e.g. via anodization of aluminum), (2) plasmonic resonances in metal nanoparticles, and (3) spectrally selective absorption enhancement in ultrathin films, such as amorphous germanium and carbon. We provide proof-of-concept by fabricating and characterizing representative aluminum-based samples showing vivid colors throughout the visible spectral range.